Religion and technology: ethical implications of integrating artificial intelligence into religious practice and experience - Chanda, Armstrong (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2025)
Integrating Artificial Intelligence (AI) into religious practices offers both significant opportunities and ethical challenges that need to be carefully considered. As AI technologies become more embedded in daily life, their application within spiritual contexts, including Christianity, Buddhism, Hinduism, and Islam, raises critical questions about privacy, data security, authenticity, and the commodification of sacred experiences. This study examines the ethical issues raised by AI in religious settings and explores ways to address them. The goal is to create a balanced approach that takes advantage of technology's benefits while respecting religious beliefs. Guided by the ethical framework of Principlism theory, including not harming (non-maleficence), doing good (beneficence), fairness (justice), and freedom (autonomy), the research employs qualitative document analysis and case studies from China, India, and Japan, to explore AI’s role in virtual worship, digital religious education, and personalised spiritual guidance. AI allows for virtual worship services, breaking down physical boundaries as witnessed globally. Its algorithms can analyse religious texts, leading to deeper comprehension. Additionally, it provides tailored guidance, which can enrich spiritual paths. By utilising AI, religious practices can become more engaging and inclusive, especially for diverse populations. The paper concludes that while AI holds transformative potential for enriching religious life, its implementation must be carefully aligned with ethical principles and cultural sensitivities to preserve the integrity and authenticity of diverse religious traditions. Future research should focus on developing ethical AI frameworks through collaboration among theologians, ethicists, and AI developers, and assess their impact on community engagement and spiritual authenticity.